A CRISPR Path to Engineering New Genetic Mouse Models for Cardiovascular Research. Issue 6 (June 2016) - Miano, Joseph M.; Zhu, Qiuyu Martin; Lowenstein, Charles J.
Abstract : Previous efforts to target the mouse genome for the addition, subtraction, or substitution of biologically informative sequences required complex vector design and a series of arduous steps only a handful of laboratories could master. The facile and inexpensive clustered regularly interspaced short palindromic repeats (CRISPR) method has now superseded traditional means of genome modification such that virtually any laboratory can quickly assemble reagents for developing new mouse models for cardiovascular research. Here, we briefly review the history of CRISPR in prokaryotes, highlighting major discoveries leading to its formulation for genome modification in the animal kingdom. Core components of CRISPR technology are reviewed and updated. Practical pointers for 2-component and 3-component CRISPR editing are summarized with many applications in mice including frameshift mutations, deletion of enhancers and noncoding genes, nucleotide substitution of protein-coding and gene regulatory sequences, incorporation of loxP sites for conditional gene inactivation, and epitope tag integration. Genotyping strategies are presented and topics of genetic mosaicism and inadvertent targeting discussed. Finally, clinical applications and ethical considerations are addressed as the biomedical community eagerly embraces this astonishing innovation in genome editing to tackle previously intractable questions. Abstract : Supplemental Digital Content is available in the text.